The Role of Subcontracting in Activating of Local Labour Market - Kukulak-Dolata, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
This article explains the meaning of subcontracting in activation of local labour markets in Poland. It was indicated what positive and negative results, subcontracting brings for handling labour market. Fundamentals of this work consist of critical study of legal acts regulating subcontracting in labour market and study of an available literature. Described model of subcontracting should be considered as open because it is going to evolve on account of how it affects professional activation of unemployed.